2012
DOI: 10.1002/jcp.24019
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear IRS‐1 and cancer

Abstract: The family of insulin receptor substrates (IRS) consists of four proteins (IRS-1 - IRS-4), which were initially characterized as typical cytosolic adaptor proteins involved in insulin receptor (IR) and insulin-like growth factor I receptor (IGF-IR) signaling. The first cloned and characterized member of the IRS family, IRS-1, has predicted molecular weight of 132 kDa, however, as a result of its extensive serine phosphorylation it separates on a SDS gel as a band of approximately 160–185 kDa. In addition to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 96 publications
(148 reference statements)
1
45
0
Order By: Relevance
“…In addition, the present study showed that phosphorylated IRS-1 was mainly distributed in the nucleus of astrocytes treated with Aβ 1-42 oligomers, which was consistent with previous results found in neurons treated with Aβ 1-42 oligomers (Ma et al, 2009). Several studies show that nuclear IRS-1 regulates the activity of the rDNA, cyclin D1 and c-myc promoters, which may contribute to cell proliferation and cell cycle progression in PI3K independent pathway (Tu et al, 2002;Chen et al, 2005;Wu et al, 2008;Reiss et al, 2012). In addition, a recent study shows that IRS-1 is associated with small nuclear RNA that contributes to ribosome biogenesis (Ozoe et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the present study showed that phosphorylated IRS-1 was mainly distributed in the nucleus of astrocytes treated with Aβ 1-42 oligomers, which was consistent with previous results found in neurons treated with Aβ 1-42 oligomers (Ma et al, 2009). Several studies show that nuclear IRS-1 regulates the activity of the rDNA, cyclin D1 and c-myc promoters, which may contribute to cell proliferation and cell cycle progression in PI3K independent pathway (Tu et al, 2002;Chen et al, 2005;Wu et al, 2008;Reiss et al, 2012). In addition, a recent study shows that IRS-1 is associated with small nuclear RNA that contributes to ribosome biogenesis (Ozoe et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The family of insulin receptor substrate proteins (IRS-1 – IRS-4) serve as intermediates in the action of cell surface receptors that, in addition to their metabolic and growth regulation functions, are implicated in malignant transformation [31, 32]. We found that the IRS-1 family member protein was down-regulated (67%).…”
Section: Resultsmentioning
confidence: 99%
“…However, discrepancies from this view, including evidence of nuclear IRS-1 localization/action [32] and its down-regulation in some tumors [75] do exist. Our IRS-1 expression observations do not easily align with such disparate reports.…”
Section: Discussionmentioning
confidence: 99%
“…There are six members of the IRS family, of which IRS-1 is the best characterized (Reiss et al, 2012). Recent reports suggest that IRS-2 serine phosphorylation is increased and total IRS-2 level is decreased in a 6-hydroxydopamine (OHDA) PD animal model (Morris et al, 2008), while other studies have shown that total IRS-1 was decreased in a 6-OHDA cell model of PD (Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%